2001
DOI: 10.1080/02827580152496687
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Affecting Ex Vitro Performance of Somatic Embryo Plants of Picea abies

Abstract: The potential to use somatic embryos for large-scale propagation of elite genotypes, for integration into breeding programmes and for connecting breeding and mass propagation, is receiving much attention. However, before the methods are applied it is important that the plants regenerated via somatic embryogenesis grow as expected, i.e. as seedlings or cuttings. Growth of somatic embryo plants is under a cumulative in uence of a number of treatments given during the in ×itro phase and during the ex ×itro establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…To date, for some conifer species, the effect of various environmental factors on the germination of somatic embryos has been studied (Uddin et al 1989;Webster et al 1990;Hay and Charest 1999;Hogberg et al 2001). Some of the first factors studied were: medium composition, light versus dark culture, and position of embryos on the media (Uddin et al 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, for some conifer species, the effect of various environmental factors on the germination of somatic embryos has been studied (Uddin et al 1989;Webster et al 1990;Hay and Charest 1999;Hogberg et al 2001). Some of the first factors studied were: medium composition, light versus dark culture, and position of embryos on the media (Uddin et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the first factors studied were: medium composition, light versus dark culture, and position of embryos on the media (Uddin et al 1989). In later studies, more attention was paid to the effect of procedures applied during the development of somatic embryos of Norway spruce (Picea abies) from embryogenic tissue on their subsequent ability to germinate (Bozhkov and von Arnold 1998;Hogberg et al 2001). Bozhkov and von Arnold (1998) demonstrated that polyethylene glycol (PEG) added to the medium at the stage of formation of embryos from embryogenic tissue of P. abies had an inhibitory effect on further development of somatic embryos.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of embryogenic tissue contact with ABA affects not only the number of formed embryos but also their later development (germination, conversion into plantlets and adaptation to ex vitro conditions). Treatment with ABA for 5 weeks is sufficient to stimulate development of Norway spruce embryos into mature forms (Filonova et al 2000b;Bozhkov and von Arnold 1998;Hogberg et al 2001). Our results show that in spruces the largest numbers of mature somatic embryos were developed if the basal medium was supplemented with 20-40 µM ABA and 1 µM IBA and the cultures were kept in dim light (25-30 µE m -2 s -1 ) for 5 weeks.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 58%
“…The reason for that was not explored in this study; however, we speculate that the difference in growth can be attributed to the culture conditions of somatic plants. Similarly, Bozhkov and von Arnold (1998) and Högberg et al (2001) reported inferior growth increment in somatic plants versus that in seedlings of Picea abies. For the same species, Cyr et al (1991) reported that the differences between somatic plants and seedlings occurred early during plant development.…”
Section: Discussionmentioning
confidence: 99%
“…However, height increments were similar for both plant types Major 1994a, 1994b). Högberg et al (2001) found that the after effects of culture conditions could be avoided by modifying the procedure of somatic embryogenesis. In addition, epicotyl length and presence of lateral roots as combined selection criteria at ex vitro transfer could be used to identify somatic plants having height growth characteristics comparable to those of seedlings.…”
Section: Discussionmentioning
confidence: 99%